PEMBERIAN TRICHOKOMPOS TANDAN KOSONG KELAPA SAWIT (TKKS) PADA MEDIUM TANAM TERHADAP PERTUMBUHAN KAKAO (Theobroma cacao L.) - Cica Yulia Mandela1; Fetmi Silvina (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2018)
The research aimed to determine the effect of oil palm empty fruit bunches trichokompos and to get the best dose in the embedding medium on the growth of cocoa. This research has been conducted at the experimental farm, Agriculture Faculty of Riau University. This research was conducted during the four months from July to October 2016. The research arranged experimentally by using Completely Randomized Design with 4 treatments and 5 replications. Treatment research was dose consisting of : (12.5 g/polybag, 25 g/polybag, 37.5 g/polybag, 50 g/polybag,). The observed parameters were a plant height, leaf number, stem diameter, leaf area, shoot root ratio and dry weight. The results showed that the oil palm empty fruit bunches trichokompos effect on the parameters of plant height, number of leaves, leaf area, and the dry weight. Giving trichokompos oil palm empty fruit bunches (37.5 to 50) g/polybag showed better growth on the cacao seeds. Keywords : cacao, trichokompos, oil palm empty fruit bunches.